Author Correction: Exploring the pathology of an epidermal disease affecting a circum-Antarctic sea star - Laura Núñez-Pons; Thierry M. Work; Carlos Angulo-Preckler; Juan Moles; Conxita Avila (Scientific Reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.